Determinants of Organizational Commitment through Job Satisfaction as an Intervening Variable: Determinan Komitmen Organisasi melalui Kepuasan Kerja sebagai Variabel Intervening - Nuraeni; Sulaeman, Suhendar; Rohmanulloh, Estu; M. Yusuf; Nasri, Rifzaldi (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this research is to analyze the effect of Employee Engagement, Quality of Work Life on Organizational Commitment through Job Satisfaction as an intervening variable of PT. Communication This type of research is quantitative. The source of this research data is primary data that comes from the sample, namely the employees of PT. communication. The sampling technique in this study used saturated sampling which was distributed to all employees as many as 97 respondents. This study uses the path analysis method (path analysis) which is obtained using the Smart PLS application. The results of this study indicate that Employee Engagement, and Quality of Work Life have a positive and significant effect partially and simultaneously on Job Satisfaction. And Employee Engagement, Quality of Work Life, and Job Satisfaction have a positive and significant effect partially and simultaneously on Organizational Commitment, and it can be concluded that the Satisfaction variable as an intervening variable can mediate Employee Engagement, and Quality of Work Life has a positive and significant effect on Organizational Commitment. at PT. communication.